Nitrogen and oxygen dual-doped porous carbons prepared from pea protein as electrode materials for high performance supercapacitors. (4th October 2018) - Demir, Muslum; Ashourirad, Babak; Mugumya, Jethrine H.; Saraswat, Sushil K.; El-Kaderi, Hani M.; Gupta, Ram B.
Abstract: Porous carbons as electrode materials are highly desired for use in energy storage/conversion devices. Herein, the development of a series of highly porous nitrogen and oxygen co-doped carbons by using pea protein (PP) as a cost-effective, sustainable and nitrogen-rich precursor is reported. Pea protein derived carbons (PPDCs) have been prepared by applying a straightforward two-step synthetic route including pyrolysis and KOH-chemical activation. Potassium hydroxide has been employed to generate porosity and introduce oxygen functionalities into the framework of carbon. The heteroatoms doping content and porosity parameters have been tuned by varying the synthesis temperature and activator to precursor ratio. The carbon obtained with optimal synthetic parameters (T = 800 °C and KOH/Precursor = 4) featured the highest surface area, the maximal pore volume and N-/O doping level of 3500 m 2 g −1, 1.76 cm 3 g −1, and 2.5-/17.9 at%, respectively. PPDC-4-800 as supercapacitor presented a very high specific capacitance (413 F g −1 at 1.0 A g −1 in 1 M KOH), remarkable cycling stability (92% retention after 20000 cycles) and outstanding rate capability (210 F g −1 at 30 A g −1 ). The cooperative effects of the well-developed porous architecture and surface modification of PPDCs resulted in enhanced electrochemical performances, suggesting their potential application for energy storage devices. Graphical abstract: Highlights: Carbon electrode material from pea protein. Carbonization and activation. Duel doping of nitrogen and oxygen. High surface area and high electrical capacitance.